Construction of 3D porous MXene supercapacitor electrode through a dual-step freezing strategy. (May 2022) - Gao, Guangying; Yang, Song; Wang, Shulan; Li, Li
Abstract: As an emerging two-dimensional material, MXene holds great potential for high-performance energy storage due to its tunable composition and unique physicochemical properties. However, the nanosheet-restacking issues strongly limit its actual performances. Different from the conventional one-step ice-templating method that always suffers from non-uniform layering, herein, we propose a rationally-designed dual-step freezing strategy to fabricate the 3D porous MXenes. By controlling temperatures and cooling rates for adjusting the freezing kinetics, the 3D porous MXene with large interlayer spacing and homogeneous layered structure is assembled from 1) isotropic-spacer support (nucleation-control freezing) and 2) layered expansion (growth-dominant freezing) steps. Profited from the structural advantages with expanded interlayer spacing and sufficient exposed active sites, the synthesized material delivered an outstanding capacitance for Ti3 C2 Tx MXenes and excellent device performances. This work marks a step ahead towards the facile fabrication of high-performance MXenes for potentially broad applications in energy storage fields. Graphical abstract: Image, graphical abstract